Resin-mixed non-flammable calcium silicate molding
The resin-mixed non-combustible calcium silicate molding, with xonotlite-based calcium silicate and specific additives, addresses moldability, cutting precision, and combustibility issues, offering high strength and non-combustibility for artificial wood applications.
Patent Information
- Application Number
- JP2022575521
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-01-13
- Filing Date
- 2021-12-28
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2041-12-28
AI Technical Summary
Existing calcium silicate molded products face issues with moldability, cutting workability, resistance to corner chipping, machinability, and combustibility, particularly when used as artificial wood for interior construction.
A resin-mixed non-combustible calcium silicate molding composed of xonotlite-based calcium silicate, latex, inorganic fibrous particles, glass fibers, and a coagulant, with specific proportions to achieve high specific strength, good moldability, cutting surface precision, and processability.
The resin-mixed non-combustible calcium silicate molding achieves a balance of high specific strength, excellent cutting surface accuracy, and non-combustibility, addressing the limitations of previous technologies.
Smart Images

Figure 0007646229000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin-mixed noncombustible calcium silicate molded article. [Background technology]
[0002] Calcium silicate molded bodies are used in a variety of fields, including as interior undercoats, artificial wood, construction materials, housing equipment, and base materials for molding forms for carbon fiber products. For example, artificial wood made of calcium silicate moldings used as formwork materials has traditionally been used as a material to compensate for the shortcomings of wood used as formwork materials, such as a lack of heat resistance, dimensional stability, and uniform cutting workability.
[0003] For example, Patent Document 1 discloses a calcium silicate molded product (paragraph 1) obtained by molding and drying an aqueous slurry containing 100 parts by weight of calcium silicate hydrate, 5 to 30 parts by weight (as solid content) of a styrene-butadiene copolymer latex containing a carboxyl group, a cationic polymer flocculant, and water, and also discloses that the aqueous slurry contains reinforcing fibers such as glass fibers. Patent Document 2 discloses a model material (claim 1) characterized in that the xonotlite-based calcium silicate molded body has a composition of 60 to 94 parts by weight of xonotlite-based calcium silicate hydrate, 5 to 30 parts by weight of styrene-butadiene copolymer, and 1 to 10 parts by weight of glass fiber.
[0004] Patent Document 3 discloses a calcium silicate molded body (claim 1) obtained by molding and drying a calcium silicate hydrate slurry composition consisting of 100 parts by weight of a mixture of 70-99 parts by weight of calcium silicate hydrate and 1-30 parts by weight of wollastonite, 1-30 parts by weight of reinforcing fiber, 1-40 parts by weight of latex, 1-15 parts by weight of an expanding material, and water, and specifically discloses that glass fiber can be used as the reinforcing fiber. In addition, paragraph
[0019] of Patent Document 3 also describes that "As the expanding material, at least one expanding agent selected from the group consisting of K type, M type, and S type of the ACI classification, which is a substance that reacts with water to generate ettringite, calcium sulfoaluminate-based clinker alone or in mixture with gypsum, or a mixture of aluminate-based clinker and gypsum, a substance containing blast furnace slag powder or aluminum hydroxide, a mixture of gypsum, slaked lime, or quicklime, a mixture of alumina cement and gypsum, etc. can be used."
[0005] Patent Document 4 discloses a mold substrate for CFRP molding, which contains (A) calcium silicate hydrate as a binder, (B) glass fiber, and (C) an inorganic filler including a slipping material, in which the CaO / SiO2 molar ratio of the calcareous raw material and the siliceous raw material constituting the calcium silicate hydrate as the binder is in the range of 0.7 to 1.2, the total content of the calcareous raw material and the siliceous raw material is 40 to 89 mass% relative to the total solid content, the glass fiber content is 1 to 10 mass% relative to the total solid content, the inorganic filler content is 10 to 59 mass% relative to the total solid content, the slipping material content is 0.1 to 20 mass% relative to the total solid content, and the mold substrate for CFRP molding has a bulk density of 0.6 to 1.1 (claim 1), and also discloses that talc can be used as the slipping material.
[0006] Patent Document 5 discloses a calcium silicate molded body obtained by mixing a mixture containing a calcareous raw material and a siliceous raw material with water and forming a calcium silicate hydrate slurry by hydrothermal reaction, and then molding and drying the resulting slurry. The calcium silicate molded body (claim 1) contains dispersed microcapsules encapsulating a functional substance having at least one function selected from the group consisting of aromatic, deodorant, antibacterial and insect repellent properties, and discloses that inorganic fibers such as glass fibers and polymer binders such as styrene-butadiene copolymers can be used as reinforcing materials.
[0007] Cited Document 6 discloses a method for producing a calcium silicate polymer composite board (claim 1), which comprises mixing 100 parts by weight of calcium silicate hydrate having a sedimentation volume of 10 ml / g or more, 3 to 15 parts by weight of styrene-butadiene latex, 1 to 5% by weight of cellulose fiber having a freeness of 350 ml or less as a slurry solid content, 1 to 20% by weight of a cationic latex fixing agent based on the weight of the styrene-butadiene latex, and water to obtain a slurry with a solid content concentration of 0.5 to 4% by weight, and when pouring the slurry into a papermaking vat, further dropping an anionic polymer flocculant in an amount in the range of 20 to 10,000 ppm of the solid content of the slurry to produce a paper.
[0008] Patent Document 7 discloses a calcium silicate molded body (claim 1) obtained by molding a slurry consisting of 100 parts by weight of calcium silicate, 2 to 8 parts by weight of reinforcing fiber, 3 to 9 parts by weight of latex, and 1 to 6 parts by weight of a fibrous dispersion material, in which the reinforcing fiber is glass fiber and pulp is used as the fibrous dispersion material.
[0009] Furthermore, in Japanese Patent Application No. 2019-182649, the applicant has filed a resin-mixed calcium silicate shaped body (Claim 1), which contains 50 to 80 mass% xonotlite-based calcium silicate, 5 to 20 mass% latex, 1 to 4 mass% talc, 10 to 20 mass% inorganic fibrous particles, and 1 to 10 mass% glass fiber, and contains an external proportion of 0.5 to 3 mass% of a flocculant; the resin-mixed calcium silicate shaped body (Claim 2), in which the inorganic fibrous particles are one or more types of acicular particles selected from the group consisting of wollastonite, magnesium sulfate, gypsum, and calcium carbonate; and the resin-mixed calcium silicate shaped body (Claim 3), in which the average particle size of the xonotlite-based calcium silicate is in the range of 20 to 70 μm. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Japanese Patent Application Publication No. 60-246251 [Patent Document 2] Japanese Patent Application Publication No. 5-246752 [Patent Document 3] Japanese Patent Application Publication No. 8-12409 [Patent Document 4] JP 2017-132670 A [Patent Document 5] Japanese Patent Application Publication No. 10-251052 [Patent Document 6] Japanese Patent Application Publication No. 1-224253 [Patent Document 7] Japanese Patent Application Publication No. 6-234559 Summary of the Invention [Problem to be solved by the invention]
[0011] Here, the calcium silicate molded product disclosed in Patent Document 1 has improved strength compared to inorganic calcium silicate molded products of similar density, but has problems with moldability, cutting workability, and resistance to corner chipping. Furthermore, the model material disclosed in Patent Document 2 is an attempt to accommodate larger molded products by blending glass fibers, but has problems with machinability and resistance to corner chipping. Furthermore, although the calcium silicate molding disclosed in Patent Document 3 has improved machinability and resistance to corner chipping due to the incorporation of wollastonite, its moldability is insufficient, and further improvement is required due to the increasing demand for precision machining today. In addition, the mold base material for CFRP molding disclosed in Patent Document 4 has improved machinability and resistance to corner chipping, but since it is intended for repeated use at higher temperatures than the resin-mixed calcium silicate molding of the present invention, a moist heat curing step using an autoclave is required. In addition, in order to obtain the required strength, the density needs to be increased, resulting in a problem that the mold base material is heavier than the resin-mixed calcium silicate molding.
[0012] D5 discloses a calcium silicate molded body in which the effects of functional substances having aromatic or other properties are not impaired even when the body is subjected to processing such as cutting or machining, but the moldability is not sufficient. Patent Document 6 discloses a method for producing calcium silicate polymer composite boards with the aim of improving productivity, strength, and processability. However, this method is based on a papermaking process and uses combustible pulp as the raw material. Patent Document 7 discloses a calcium silicate molded body having water resistance, fire resistance and sufficient bending strength, but uses a flammable fibrous dispersion material and latex in combination.
[0013] Here, the problem of Japanese Patent Application No. 2019-182649 is to provide a resin-mixed calcium silicate molded body that has a high specific strength, a small heat shrinkage rate, and excellent cutting surface accuracy and processability, and in order to solve this problem, the resin-mixed calcium silicate molded body of Japanese Patent Application No. 2019-182649 contains 5 to 20 mass% latex. However, when a resin-mixed calcium silicate molded body containing 5 to 20 mass% latex is used as a building material, particularly as an artificial wood for interior construction, a problem occurs in terms of its required performance of non-combustibility.
[0014] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a resin-mixed non-combustible calcium silicate molding which has a high specific strength and a good balance between moldability, cutting surface precision, processability, and non-combustibility. [Means for solving the problem]
[0015] The resin-mixed non-flammable calcium silicate shaped body of the present invention is a resin-mixed non-flammable calcium silicate shaped body containing a raw material mixture containing xonotlite-based calcium silicate, latex, inorganic fibrous particles and glass fibers, and a coagulant, and is characterized in that the raw material mixture contains 65 to 90 mass % of xonotlite-based calcium silicate, 1 mass % or more and less than 5 mass % of latex, 8 to 20 mass % of inorganic fibrous particles and 1 to 10 mass % of glass fibers relative to the total amount of the raw material mixture, and contains 0.5 to 3 mass parts of coagulant per 100 mass parts of the raw material mixture. Incidentally, the "total amount of the raw material blend" means the "total amount of the raw material blend (solid content)."
[0016] In the resin-mixed noncombustible calcium silicate molding of the present invention, the inorganic fibrous particles are preferably acicular particles of one or more types selected from the group consisting of wollastonite, magnesium sulfate, gypsum and calcium carbonate, and are more preferably wollastonite.
[0017] In the resin-mixed noncombustible calcium silicate shaped article of the present invention, the average particle size of the xonotlite-based calcium silicate is preferably within the range of 20 to 70 μm.
[0018] The resin-mixed noncombustible calcium silicate shaped article of the present invention may further contain 1 to 4% by mass of talc based on the total amount of the raw material blend. The present invention also provides an artificial wood material comprising any one of the above-mentioned resin-mixed noncombustible calcium silicate moldings. Effect of the Invention
[0019] According to the present invention, it is possible to obtain a resin-mixed noncombustible calcium silicate molding having a high specific strength and a good balance between moldability, cutting surface precision, processability, and noncombustibility. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The resin-mixed non-flammable calcium silicate shaped article of the present invention is characterized by containing xonotlite-based calcium silicate, latex, inorganic fibrous particles, glass fibers, a flocculant, and optionally talc in specific proportions.
[0021] In the resin-mixed non-combustible calcium silicate molded body of the present invention, the content of xonotlite-based calcium silicate is within the range of 65-90 mass%, preferably 70-85 mass%, more preferably 72-85 mass%, even more preferably 74-85 mass%, even more preferably 74-82 mass%, and most preferably 74-80 mass% based on the total amount of the raw material mixture. Here, if the content of xonotlite-based calcium silicate is less than 65 mass%, it is not preferable because the processability may decrease. Also, if the content of xonotlite-based calcium silicate is more than 90 mass%, it is not preferable because there is no room for mixing other components and sufficient density and bending strength cannot be obtained.
[0022] The average particle size of the xonotlite-based calcium silicate is not particularly limited as long as the effects of the present invention are achieved, but is preferably within the range of 20 to 70 μm, more preferably 40 to 65 μm, and even more preferably 40 to 60 μm. If the average particle size of the xonotlite-based calcium silicate is less than 20 μm, the moldability of the resin-mixed noncombustible calcium silicate molded body may deteriorate, making it difficult to produce the molded body. If the average particle size of the xonotlite-based calcium silicate is more than 70 μm, the cutting surface accuracy and processability of the resin-mixed noncombustible calcium silicate molded body may deteriorate. The average particle size of the xonotlite-based calcium silicate described in this specification is obtained by measuring the particle size distribution of xonotlite-based calcium silicate particles by a laser diffraction / scattering method using a laser diffraction particle size distribution analyzer SALD-2200 manufactured by Shimadzu Corporation.
[0023] Next, in the resin-mixed non-combustible calcium silicate shaped body of the present invention, the content of latex is in the range of 1% by mass or more and less than 5% by mass, preferably 2.0 to 4.8% by mass, and more preferably 2.5 to 4.8% by mass, based on the total amount of the raw material mixture. Here, if the content of latex is less than 1% by mass, it is not preferable because the strength development effect cannot be imparted to the resin-mixed non-combustible calcium silicate shaped body. Also, if the content of latex is 5% by mass or more, it is not preferable because the non-combustibility is deteriorated. As the latex, for example, a latex having an unsaturated carbon bond in the main chain is suitable, and butadiene rubber, chloroprene rubber, styrene-butadiene rubber, styrene rubber, nitrile rubber, butyl rubber, etc. can be used, and it is preferable to use styrene-butadiene rubber.
[0024] Next, in the resin-mixed noncombustible calcium silicate shaped body of the present invention, the content of the inorganic fibrous particles is within the range of 8-20% by mass, preferably 8-18% by mass, more preferably 9-16% by mass, and most preferably 10-15% by mass, based on the total amount of the raw material mixture. Here, if the content of the inorganic fibrous particles is less than 8% by mass, the moldability of the resin-mixed noncombustible calcium silicate shaped body is significantly reduced, which is not preferable. Also, if the content of the inorganic fibrous particles exceeds 20% by mass, the cutting surface accuracy and processability of the obtained resin-mixed noncombustible calcium silicate shaped body are reduced, which is not preferable. In addition, as the inorganic fibrous particles, needle-shaped particles such as wollastonite, magnesium sulfate, gypsum, and calcium carbonate can be used, and it is preferable to use wollastonite.
[0025] In the resin-mixed non-combustible calcium silicate molded product of the present invention, the glass fiber content is within the range of 1-10% by mass, preferably 2-8% by mass, and more preferably 3-6% by mass, based on the total amount of the raw material mixture. If the glass fiber content is less than 1% by mass, sufficient material strength cannot be obtained, which is undesirable. If the glass fiber content is more than 10% by mass, the cutting surface accuracy and processability of the resulting resin-mixed calcium silicate molded product are reduced, which is undesirable.
[0026] The resin-mixed non-flammable calcium silicate molded product of the present invention may contain talc in the range of 1 to 4 mass%, preferably 1 to 3 mass%, based on the total amount of the raw material mixture. By adding talc in the above content range, the cutting surface precision is improved. Note that talc may have a negative effect on moldability, and in particular, if the talc content exceeds 4 mass%, moldability may be significantly reduced.
[0027] The raw material blend of the present invention contains xonotlite-based calcium silicate, latex, inorganic fibrous particles and glass fibers as essential components in the above-mentioned contents, and may further contain talc in the above-mentioned content range. Furthermore, the raw material blend of the present invention may contain components that may normally be contained in calcium silicate shaped bodies, as long as the effects of the present invention are not impaired.
[0028] On the other hand, it is preferable that the raw material blend of the present invention does not contain any combustible raw materials other than latex (for example, the pulp described in Patent Document 6, the fibrous dispersion material described in Patent Document 7, etc.). It is also preferable that the raw material blend of the present invention does not contain the expansion agent described in Patent Document 3. Therefore, the resin-mixed non-combustible calcium silicate shaped body of the present invention preferably contains a raw material blend consisting of xonotlite-based calcium silicate, latex, inorganic fibrous particles, and glass fibers in the above-specified amounts.Similarly, the resin-mixed non-combustible calcium silicate shaped body of the present invention preferably uses a raw material blend consisting of xonotlite-based calcium silicate, latex, inorganic fibrous particles, glass fibers, and talc in the above-specified amounts. In other words, in the raw material blend of the present invention, it is preferable to adjust the content of each of the xonotlite-based calcium silicate, latex, inorganic fibrous particles and glass fibers so that the total content of each of the components is 100 mass % based on the total amount of the raw material blend. Similarly, it is preferable to adjust the content of each of the xonotlite-based calcium silicate, latex, inorganic fibrous particles, glass fibers and talc in the raw material mixture of the present invention so that the total content of each of the components is 100 mass% based on the total amount of the raw material mixture.
[0029] Next, the resin-mixed non-combustible calcium silicate shaped body of the present invention contains 0.5 to 3 parts by mass, preferably 0.8 to 2.5% by mass of a flocculant relative to 100 parts by mass of the raw material mixture containing the above-mentioned xonotlite-based calcium silicate, latex, inorganic fibrous particles, and glass fiber, and optionally talc. Here, if the content of the flocculant is less than 0.5 parts by mass relative to 100 parts by mass of the raw material mixture, it is not preferable because the effect cannot be exerted. Also, even if the content of the flocculant exceeds 3 parts by mass relative to 100 parts by mass of the raw material mixture, it is not preferable because there is no corresponding effect. The flocculant is preferably a cationic type, and a cationic polymer flocculant mainly composed of an aliphatic amine having a quaternary ammonium group capable of interacting with the functional group of the latex used, such as a polydiallylamine type, a polyacrylamide type, a polymethylacrylamide type, or a polyacrylic acid ester type, can be used. Examples of flocculants that can be used include the Himolock (registered trademark) series manufactured by Himo Corporation, the Orflock (registered trademark) series manufactured by Organo Corporation, the Aronflock (registered trademark) E series manufactured by MT Aquapolymer Co., Ltd., and the Sanflock (registered trademark) series manufactured by Sanyo Chemical Industries, Ltd.
[0030] In addition, in order to suppress foaming during production of the resin-mixed noncombustible calcium silicate molded body of the present invention, an antifoaming agent may be used. The content of the antifoaming agent is not particularly limited as long as it does not impair the effects of the present invention, but it is preferably 0.01 to 3 parts by mass, more preferably 0.05 to 1 part by mass, relative to 100 parts by mass of the raw material mixture. By mixing the antifoaming agent within the above range, foaming during production can be suppressed while maintaining the physical properties such as strength of the resin-mixed noncombustible calcium silicate molded body of the present invention. Examples of antifoaming agents that can be used include SN DEFORMER series manufactured by SAN NOPCO LTD., FOAMLEX (registered trademark) series manufactured by NICCA CHEMICAL CO., LTD., and CURIRES (registered trademark) series manufactured by Kurita Water Industries Ltd.
[0031] In order to obtain a resin-mixed noncombustible calcium silicate shaped body that has a high specific strength and a good balance between moldability, cutting surface precision, processability, and noncombustibility, the resin-mixed noncombustible calcium silicate shaped body of the present invention preferably comprises a raw material mixture consisting of 65 to 90 mass% xonotlite calcium silicate, 1 mass% or more and less than 5 mass% latex, 8 to 20 mass% inorganic fibrous particles, and 1 to 10 mass% glass fibers, relative to the total amount of the raw material mixture, 0.5 to 3 mass parts of a coagulant relative to 100 parts by mass of the raw material mixture, and 0.01 to 3 mass parts of an antifoaming agent relative to 100 parts by mass of the raw material mixture. For the same reason, the resin-mixed nonflammable calcium silicate shaped body of the present invention preferably comprises a raw material mixture consisting of 65 to 85 mass% xonotlite-based calcium silicate, 1 mass% or more but less than 5 mass% latex, 8 to 20 mass% inorganic fibrous particles, 1 to 10 mass% glass fiber, and 1 to 4 mass parts of talc, relative to the total amount of the raw material mixture, 0.5 to 3 mass parts of a flocculant, and 0.01 to 3 mass parts of an antifoaming agent, relative to 100 parts by mass of the raw material mixture. However, in this case, it is not excluded that the resin-mixed noncombustible calcium silicate shaped product of the present invention contains inevitable impurities derived from the raw material components. The inevitable impurities are preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less, based on the total amount of the resin-mixed noncombustible calcium silicate shaped product of the present invention.
[0032] The method for producing the resin-mixed non-combustible calcium silicate molded article made of the above-mentioned components is not particularly limited, but it can be produced, for example, by pressurized dehydration molding using a steel mold. EXAMPLES
[0033] A raw material mixture excluding the flocculant was prepared in the mixing ratio shown in the table below, the water content was adjusted so that it was 8 to 9 times the solid content of the raw material mixture, and mixed. Next, the flocculant was added to 100 parts by mass (solid content) of the raw material mixture in the ratio shown in Table 1, and mixed to prepare a raw material slurry. The obtained slurry was poured into a steel mold with a width of 300 mm, length of 300 mm, and height of 150 mm, and a pressure of 5 to 10 N / mm was applied. 2 After dehydration press molding by applying a pressure of 1000 psi, the obtained raw board was dried at 110 to 140°C for more than 24 hours and cut into a width of 75 mm and a length of 300 mm to obtain a test specimen with a thickness of 10 mm.
[0034] [Table 1]
[0035] In the table, As the "latex," we used a styrene-butadiene copolymer latex containing carboxyl groups with a glass transition temperature of 40°C or less (product name: Styrene-Butadiene Latex 0696, manufactured by JSR Corporation); As the "flocculant", a cationic polymer flocculant (product name: Himoloc Q-700, manufactured by Himo Corporation) was used; The defoamer used was SN Deformer 265 (manufactured by San Nopco Ltd.). The amounts of the flocculant and defoamer are listed based on 100 parts by mass of the raw material blend.
[0036] "Moldability" is an index that evaluates the pressure dehydration molding sensitively, and is the maximum value when the pressing pressure is 10N / mm 2 Below, a condition in which there was absolutely no leakage of slurry from the mold was indicated by ◎, a condition in which only slight leakage of slurry was observed was indicated by ○, and a pressing pressure of 10 N / mm 2 When the test result exceeds the limit and a large amount of slurry leakage is observed, the test result is indicated as ×. "Density" is measured according to the method of JIS A 9510; "Flexural strength" was measured using a method conforming to JIS A 9510; "Specific strength" is the bending strength divided by the square of the density; "Cutting surface precision" was evaluated by the feel of the cutting surface, with ◎ indicating that the cutting surface is smooth and beautiful, ◯ indicating that the cutting surface is mostly smooth with only slight roughness, △ indicating that the cutting surface is slightly rough but can be smoothed by simple processing such as wiping off the surface, and × indicating that the cutting surface is rough. "Workability" indicates the ease of cutting the test piece with a general NC router. ○ indicates that the resistance during cutting is low and the piece can be easily cut, △ indicates that the piece can be cut with some resistance, and × indicates that the surface collapses, such as chipping, during cutting. "Non-flammable" is evaluated in accordance with JIS A 5430 (Appendix JA) by heating for 20 minutes using a cone calorimeter test, and ◎ indicates a total calorific value of 6MJ / m 2 The following items have a total calorific value of 6MJ / m 2 Exceeds 8MJ / m 2 The following is indicated by an X: the total calorific value is 8 MJ / m 2 Each indicates something that exceeds the above. [Industrial Applicability]
[0037] The resin-mixed noncombustible calcium silicate molded product of the present invention can be used as artificial wood in various fields such as interior base material and construction material.
Claims
1. A resin-mixed non-flammable calcium silicate shaped body containing a raw material mixture containing xonotlite-based calcium silicate, latex, inorganic fibrous particles, and glass fibers, and a flocculant, the raw material mixture containing, relative to the total amount of the raw material mixture, 65 to 90 mass % of xonotlite-based calcium silicate, 1 mass % or more and less than 5 mass % of latex, 8 to 20 mass % of inorganic fibrous particles, and 1 to 10 mass % of glass fibers, and containing, relative to 100 mass parts of the raw material mixture, 0.5 to 3 mass parts of the flocculant.
2. 2. The resin-mixed noncombustible calcium silicate shaped product according to claim 1, wherein the inorganic fibrous particles are acicular particles of one or more types selected from the group consisting of wollastonite, magnesium sulfate, gypsum and calcium carbonate.
3. 3. The resin-mixed noncombustible calcium silicate molding according to claim 1, wherein the inorganic fibrous particles are wollastonite.
4. 4. The resin-mixed noncombustible calcium silicate molded body according to claim 1, wherein the average particle size of the xonotlite-based calcium silicate is within the range of 20 to 70 μm.
5. The resin-mixed noncombustible calcium silicate shaped body according to any one of claims 1 to 4, wherein the raw material mixture further contains 1 to 4 mass% of talc based on the total amount of the raw material mixture.
6. An artificial wood material comprising the resin-mixed noncombustible calcium silicate molding according to any one of claims 1 to 5.
Citation Information
Patent Citations
Calcium silicate moldings
JP1985246251A
Fiber-reinforced calcium silicate formed matter
JP1988260847A
Aqueous slurry for calcium silicate hydrate and calcium silicate molded article made from slurry
JP1989119554A
Production of calcium silicate-polymer composite board
JP1989224253A
Model material
JP1993246752A